A Bibliometric Literature Review of Digital Supply Chain: Trends, Insights, and Future Directions - Manal Benatiya Andaloussi (SAGE Open, 2024)
This paper presents a comprehensive bibliometric literature review that aims to analyze and synthesize the existing research on the digital supply chain. By employing a bibliometric approach, this study provides insights into the trends, key research themes, influential authors, and relevant journals in the field of DSC. Furthermore, it explores the geographical distribution of publications, collaboration networks among researchers, and the evolution of research topics. The comprehensive bibliometric analysis of literature in DSC is performed through data visualization and content analysis. Data visualization enables the analysis of publication performance and science mapping by examining prolific journals, authors, countries, influential papers, and conducting citation, co-citation, and bibliographic coupling analyses. Content analysis is carried out by examining the occurrence and clustering of textual data. The bibliometric literature review and content analysis were carried out on 114 documents indexed in the Scopus database, which were selected using the Prisma protocol. The data visualization analysis of the literature review through VOSviewer draws the landscape of scholarly research in the digital supply chain. Based on the research landscape, the content analysis demonstrates the significant effects that the incorporation of digital technology into supply chain management has had on several important research topics. The main research trends in digital supply chain according to the content analysis are: intelligent supply chain management, technologies to drive supply chains performance, circular supply chains, information reliability in supply chains, and sustainable supply chains. The findings of this review highlight the transformative potential of digital technologies in supply chain management and its performance optimization.